The effect of swaddling on infant sleep and arousal: A systematic review and narrative synthesis - Dixley, Allison; Ball, Helen L. (Frontiers in Pediatrics, 2022)
Background Western parents swaddle infants to promote sleep and reduce night-waking, however recent evidence of the effects of swaddling on the sleep of healthy infants has not been systematically reviewed. Objective To investigate the effect of swaddling on the sleep of infants up to 1 year of age using a narrative synthesis approach. Data Sources We systematically searched five academic databases, including the Cochrane trial registry (Pubmed, PsycINFO, Embase, the Cochrane library, and Blackwell Synergy). We manually searched reference lists and citations of included studies and reference lists of existing reviews. Study Selection Studies of any type, published since 2007, reporting primary data whose subjects were humans up to 12 months of age with outcome measures relating to the impact of swaddling on sleep and arousal. Data Extraction By hand using a customized template. A narrative synthesis is used to present the results. Results In total 171 studies were retrieved with 115 studies discarded at title. A further 43 were discarded at abstract, and six were discarded at full text. Two papers were combined as they reported on the same study giving a total of 6 studies that met the inclusion criteria for the review. An evidence hierarchy was used to assess Risk of Bias in the included studies; the results are presented via a narrative synthesis. Swaddling was associated with increased duration of quiet sleep in infants and a significantly reduced number of sleep state changes among infants naïve to the intervention. Limitations The integrity of the intervention (swaddling) including its baseline characteristics, was defined broadly across the included studies limiting the interpretation and transferability of the results of this review. Conclusions Swaddling appears to increase quiet sleep duration in infants and reduces the number of sleep state changes among infants naïve to the intervention. Parents should be made aware that implementing conditions unfavorable to arousability may increase SUDI risk among infant who have not previously been swaddled. This review has relevance for informing future practice recommendations and parent advice as well as in designing future studies.